Effect of fat diet on essential fatty acid metabolism of neutral lipids in rat blood serum - A. P. Levitsky; I. V. Khodakov; T. I. Pupin; A. V. Markov; I. A. Selivanskaya (Kazimierz Wielki University, 2021)
Aim. To determine the effect of dietary fats on the content and metabolism of polyunsaturated fatty acids (PUFA) in the fraction of neutral lipids blood serum. Methods. The effect of sunflower, high oleic sunflower (HOSO) and palm oils was studied when feeding rats with diets with 5 % fat for 30 days. Rats fed a fat-free diet (FFD) served as a control. The fatty acid composition of neutral blood serum lipids was determined by gas chromatography. The "activity" of fatty acid biosynthesis enzymes: elongase and desaturases was calculated from the ratio of the content of fatty acids. Results. A high content of PUFA was found in rats treated with FFD. Feeding rats with a diet with 5 % sunflower oil increased the total content of PUFAs with a slight decrease in the level of ω-3 PUFAs. Feeding rats with diets containing 5 % palm oil or HOSO did not affect the total content of PUFA, but increased the content of ω-3 PUFA. A very high "activity" of stearyl-CoA desaturase was found in rats fed FFD and fat diets. The consumption of HOSO inhibits the formation of arachidonic acid, while the consumption of palm oil enhances it. Conclusions. A high level of PUFA in neutral lipids in the blood serum of rats may indicate the presence of endogenous sources of PUFA. The optimal (for rats) consumption of dietary fats has a small effect on the content and metabolism of PUFA, with the exception of sunflower oil, the consumption of which significantly increases the ω-6/ω-3 PUFA ratio.